MEDICAL INFORMATION STANDARDS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the consideration of a wide range of issues related to the standardization of the field of medical informatics. Almost all existing standards of medical informatics are not obligatory, but recommendatory.